How “viral” social media maps can be used in geography education: An experience at a basic education institution in Santa Maria, Rio Grande do Sul, Brazil - Petsch, Carina; Delevati Ben, Franciele; Lampert Batista, Natália (Geografares, 2025)
This study investigates the potential of maps circulating on social media for geography instruction at the high school level, serving as an introductory exploration of School Cartography and Viral Cartography. Methodologically, a theoretical discussion was conducted concerning the relationship between geography and social media. Students were tasked with interpreting four viral maps, followed by a validation questionnaire. The students reported spending approximately 10% of their daily time on social media and consuming minimal content related to geography or maps. When encountering geography-related posts, they preferred those associated with curiosities and memes. Regarding the viral maps analyzed, students identified a lack of cartographic elements, which resulted in difficulties in cartographic communication and raised concerns about potential misinformation or “fake news”. The findings suggest that viral maps can serve as engaging resources to enhance geography lessons and support cartographic literacy through digital spaces.